PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MENULIS SISWA - Anggara, Syamfa Agny (Arabi : Journal of Arabic Studies, 2017)
The learning process has a close relationship with the influential elements that such as approaches, methods, and techniques. The purpose of this study is to describe objectively, (a) the application of writing learning using project-based learning model in the learning of Arabic in grade VII Madrasah Tsanawiyah  Nurul Huda Malang, (b) the result of improving the writing ability of Arabic language by applying project based  learning model to the students class VII Madrasah Tsanawiyah Nurul Huda Malang. This study used a classroom action plan. The results showed that the application of Arabic language learning with project-based learning model can improve the writing skills of grade VII of Madrasah Tsanawiyah Nurul Huda Malang.